Classroom Climate - Fraser, Barry (2015)
This article reviews four decades of research on classroom climate, with a major thrust on the development, validity, and use of several frequently used and extensively validated questionnaires. Another purpose is to review several lines of past classroom climate research, including evaluation of educational innovations, associations between student outcomes and classroom climate, and teachers’ action research attempts to improve their classroom climates.